(untitled) (Torani Journal of Fisheries and Marine Science, 2016)
This research was conducted to investigate the sex ratio and the first gonadal maturity size of mackerel fish (Decapterus macrosomas Bleeker 1841). Samples were taken from June to October 2013 in the sub-district of Panyula, District of East Riattang, in Bone region. Sample analysis was conducted at the Fisheries biology laboratory, Department of Fisheries, Hasanuddin University, Makassar. Sex ratio was analyzed by using chiquadrat-test whereas the first gonadal maturity size was obtained from the first size of the third-gonadal-maturity stage. There were 782 fish collected with male to female ratio 1,02:1,00. Statistically, the sex ratio from Bone waters was 1:1, in other words, it is still in a balance condition. The male fish reached gonadal maturity stage at the size of 195 mm, whereas the female at 210 mm. Keywords: sex ratio, gonadal maturity size, Mackarel fish, Bone strait.